Field-scale experiments for site-specific crop Management. Part I: Design considerations - Pringle, MJ; Cook, Simon E.; McBratney, AB (Springer, 2004)
This is a two-part paper concerned with the role of field-scale experiments in site-specific crop management (SSCM). Part I is a general introduction to experimental design for SSCM, while Part II focuses on applied analysis. All references are listed at the end of Part II. In Part I, we list the goals of SSCM-experimentation, in addition to the classes of valid experimental designs. Three general approaches are proposed for choosing experimental designs: approach A is for experiments concerning management classes, while approaches B and C are alternatives for continuous management. Approaches A and B are comparative and can be analysed with an appropriately modified ANOVA.